How far the ecowarrior will go : an ecofeminist reading of Disney’s Moana - Mala Hernawati, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article attempts to look into the fictional narrativization of women’s significant and distinctive relationship with nature in Disney’s Moana. Emphasizing the power and the unity of women and nature in Polynesian indigenous culture, Moana suggests that the destruction of nature results from exploitative and manipulative masculinity. Through ecofeminist perspectives, this essay observes that Moana offers critical views and promotes awareness of gender and environmental issues. These ideas are communicated through the visual and verbal depiction of power relations that defy patriarchal tradition alongside the expressions of protest against devaluation and abuse of nature and women. To put it in the context of the development of themes in Disney’s princess line, Moana's presence can be a novel alternative to the typical images of women, namely a new portrayal of a female character whose primary concern is not romance but instead the sustainability of the environment where she lives. This study also confirms that Disney’s animated princess films continuously adjust with the dynamics of global feminist discourse.